Contemporary international business in the Asia-Pacific region - Verbeke, Alain; Roberts, Robin E.; Delaney, Deborah; Zámborský, Peter; Enderwick, Peter; Nagar, Swati (Cambridge : Cambridge University Press, 2020)
The increasing dominance of the Asia-Pacific region as a source of international business growth has created a dynamic and complex business environment. For this reason, a sound understanding of regional economies, communities and operational challenges is critical for any international business manager working in a global context. With an emphasis on 'doing business in Asia', Contemporary International Business in the Asia-Pacific Region addresses topics that are driving international business today. Providing content and research that is accessible to local and international students, this text introduces core business concepts and comprehensively covers a range of key areas, including trade and economic development, dimensions of culture, business planning and strategy development, research and marketing, and employee development in cross-cultural contexts. Written by authors with industry experience and academic expertise, Contemporary International Business in the Asia-Pacific Region is an essential resource for students of business and management.
Part I. Core Concepts: -- 1. Foundations of international business in the Asia-Pacific region -- 2. Drivers and challenges of internationalising firms -- 3. Economics and the role of regional integration -- 4. Culture, ethics and corporate governance -- 5. International investment -- Part II. Dynamics of International Business in the Asia-Pacific Region: -- 6. Emerging economies -- 7. Market entry and development strategies -- 8. International business research -- Part III. Functional Issues: 9. Foreign currency and international financial management -- 10. International marketing -- 11. International sourcing and production -- 12. Managing managers in an Asia-Pacific environment -- 13. Ongoing challenges for international business in the Asia -- Appendix: IB skill builder
Title from publisher's bibliographic system (viewed on 14 Feb 2020).
Keywords: elektronické knihy; electronic books; International business enterprises -- Pacific Area; Pacific Area -- Foreign economic relations